THE EFFECT OF COMPETENCE, WORK ENVIRONMENT AND WELFARE ON JOB SATISFACTION OF PUBLIC HOSPITAL EMPLOYEES LANGSA REGIONAL HOSPITAL - Mona Hayati; Yusniar; Em Yusuf Is; Maisyura (RADJA PUBLIKA, 2025)
This study was conducted to examine the influence of Competence, Work Environment and Welfare on Job Satisfaction of Employees of Langsa Regional General Hospital. This type of research uses a qualitative method that is quantitative, data collection using a questionnaire containing questions and statements by distributing it to the employees concerned at Langsa Regional General Hospital. The population in this study were employees with PNS status at Langsa Regional General Hospital totaling 547 employees. While the number of samples in this study was 72 employees. The data analysis method used was multiple linear regression analysis technique using SPSS 26. Data analysis used the classical assumption test, partial test (t-test) and coefficient of determination test. The results of the study showed that Competence influenced Job Satisfaction, Work Environment influenced Job Satisfaction and Welfare influenced Job Satisfaction of Employees of Langsa Regional General Hospital (RSUD).